Complications of Mandibular Distraction Osteogenesis in Infants with Isolated Robin Sequence - Zhe Mao; Gabriel Tian; Mayank Shrivastava; Jiawei Zhou; Liang Ye (MDPI AG, 2023)
Mandibular Distraction Osteogenesis (MDO) is now the preferred procedure to alleviate airway obstruction in infants with severe Robin Sequence (RS). However, there have been very few studies investigating complications related to MDO surgery performed on patients affected by isolated RS. In this study, age at distraction, weight at distraction, preoperative intubation, repeat MDO and complications associated with MDO were included as variables. Minor, moderate and major problems were evaluated and recorded as surgical site infections (SSI), injuries to the facial nerve, self-extinction hypertrophic scars, temporomandibular joint ankylosis, device failures, early ossification and fibrous non-union. One hundred and fifty one patients with isolated RS were included. At distraction, the mean age was 72 days (12-540 days) and the mean weight was 4.05 kg (2.4-12.2 kg). Only one patient needed tracheostomy after MDO, and none required further distraction. Ultimately, the complication rate was 15.23%, and there was a total of 7.95% minor, 9.27% moderate and 0% major complications. Minor incidents included surgical site infection (SSI) managed with antibiotics taken orally (n = 8), neuropraxia in the VII cranial nerve (CN) (n = 1), and hypertrophic scarring (n = 3). Incidents reported as moderate were SSIs managed with intravenous antibiotics (n = 9), incision and drainage (n = 3) and self-extubation (n = 2). There was no case of TMJ ankylosis. There were no cases of early or premature ossification, fibrous non-union and device fracture. In conclusion, MDO is an effective and appropriate management technique for infants with isolated RS and severe airway obstruction. Infections at the surgery site accounted for the vast majority of the complications. Further investigations may be needed to determine the long-term consequences of MDO.